2021
DOI: 10.1080/1750984x.2021.1998577
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of professional identity in sport psychology

Abstract: The establishment of a strong professional identity (PI) among sport psychology practitioners (SPPs) has the potential to increase the likelihood of individual ethical working, awareness of professional roles, and ultimately, support of a more effective and lasting career. Nevertheless, there is currently no global consensus regarding a definition of sport psychology professional identity, which is imperative for ongoing advances in professional formation, training and practice. In this study, we conducted a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Nonetheless, the internship is instrumental in cultivating teachers' occupational commitment among student teachers, according to multiple studies [22], consistent with what we found. An internship allows trainee teachers to deal with an actual teaching scenario that requires interaction with students, instructors, and the inner self [23], and positive communication helps shape a professional identity [24]. Professional identity is a dynamic process to establish teachers as a profession by continuously renewing and blending professionalism, beliefs, values, and behaviors [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the internship is instrumental in cultivating teachers' occupational commitment among student teachers, according to multiple studies [22], consistent with what we found. An internship allows trainee teachers to deal with an actual teaching scenario that requires interaction with students, instructors, and the inner self [23], and positive communication helps shape a professional identity [24]. Professional identity is a dynamic process to establish teachers as a profession by continuously renewing and blending professionalism, beliefs, values, and behaviors [25].…”
Section: Discussionmentioning
confidence: 99%